PENGARUH PENGGUNAAN DANA DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR PERDESAAN: STUDI DI DESA NGERU KECAMATAN MOYO HILIR - K Kamaruddin; Novi Kadewi Sumbawati; Rahmad Hidayat (Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study was to measure the influence of the use of village funds on rural infrastructure development in Ngeru Village, Moyo Hilir District. The data used in this study is primary data obtained from research respondents through questionnaires. The number of respondents in this study was the Ngeru Village community, amounting to 95 people. The data analysis method in this study uses simple linear analysis, partial parameter hypothesis testing, and coefficient of determination test (R2). Based on the results of this study, it shows that the use of village funds has a positive and significant effect on the development of rural infrastructure in Ngeru Village, Moyo Hilir District. The ability of the village fund variable in explaining the variables of rural infrastructure development in Ngeru Village, Moyo Hilir District is 46.3%, while the remaining 53.7% is influenced by other variables outside the scope of this study.